2015
DOI: 10.2217/fca.15.60
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery and Therapeutic Impact of extended-release Acetylsalicylic Acid

Abstract: Current treatment guidelines recommend once-daily, low-dose acetylsalicylic acid (ASA; aspirin) for secondary prevention of cardiovascular events. However, the anti-thrombotic benefits of traditional ASA formulations may not extend over a 24-h period, especially in patients at high risk for a recurrent cardiovascular event. A next-generation, extended-release ASA formulation (ER-ASA) has been developed to provide 24-h anti-thrombotic coverage with once-daily dosing. The pharmacokinetics of ER-ASA indicates slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…When treated on MSCs, ASA is capable of elevating BMMSCs-mediated bone regeneration (Liu et al, 2011) and improving stem cells from human exfoliated deciduous teeth (SHED) osteogenic differentiation capacity (Liu et al, 2015). However, as ASA possessed a rapid dissolution profile and short half-life in vivo (Bliden et al, 2016), fabricating a suitable scaffold and delivery system to carry and sustain ASA efficacy at the site of bone repair is essential.…”
Section: Introductionmentioning
confidence: 99%
“…When treated on MSCs, ASA is capable of elevating BMMSCs-mediated bone regeneration (Liu et al, 2011) and improving stem cells from human exfoliated deciduous teeth (SHED) osteogenic differentiation capacity (Liu et al, 2015). However, as ASA possessed a rapid dissolution profile and short half-life in vivo (Bliden et al, 2016), fabricating a suitable scaffold and delivery system to carry and sustain ASA efficacy at the site of bone repair is essential.…”
Section: Introductionmentioning
confidence: 99%
“…To address the unmet medical need for 24-h antiplatelet coverage in high-risk populations, an extended-release aspirin (Durlaza®, New Haven Pharmaceuticals, Inc., North Haven, CT) was developed and approved in the United States in 2015. 9 In addition, ongoing studies are now investigating the utility of deleting aspirin therapy in the setting of potent P2Y 12 receptor blockade with ticagrelor or replacing it with a new oral anticoagulant.…”
Section: Aspirinmentioning
confidence: 99%
“…However, the clinical importance of this pharmacodynamic interaction remains highly controversial. 9 These investigations failed to demonstrate the utility of platelet function testing in reducing the post-PCI ischemic risk. Major criticism for the latter neutral observation are: all these investigations used the VerifyNow P2Y12 assay to assess platelet reactivity to ADP and to identify HPR, these investigations included mostly low-risk patients undergoing PCI and had resultant low event rates irrespective of platelet reactivity.…”
Section: Clopidogrelmentioning
confidence: 99%
“…Acetylsalicylic acid (ASA) is a widely used nonsteroidal anti-inflammatory drug that can affect multiple biological processes and the local microenvironment of mesenchymal stem cells in MSC-mediated bone regeneration. It can elevate the osteogenic differentiation through activation of osteoblasts and inhibition of osteoclasts ( Yamaza et al, 2008 ), but its rapid dissolution nature and short half-life greatly limit its clinical applications ( Bliden et al, 2016 ), which urgently require a suitable scaffold and drug delivery system to achieve sustainable transportation at the site of bone repair. A recent study reported an aspirin-based tetra-PEG hydrogel with a sustained release system to promote the osteogenesis performance, but simultaneously satisfying mechanics and cell proliferation is necessarily improved in bone regeneration ( Yunfan Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%